Pengelolaan Pembelajaran Tematik Kelas 2 Di Sd Muhammadiyah 3 Surakarta - Wulandari, Aprianti Diah; , Dr. Tjipto Subadi, M.Si; , Dr. Sumardi, M.Si (2017)
The purpose of this study to describe (1) the aracteristics of thematic lessonplanning, (2) the characteristics of the implementation of thematic learning, and(3) the racteristics of evaluation thematic learning in SD Muhammadiyah 3 Surakarta. This study is a qualitative research with ethnographic research design. The study was conducted in SD Muhammadiyah 3 Surakarta. The technique of collecting data using interviews, documentation, and observation. Analysis of the data using three stages: data reduction, data presentation, and drawing conclusions. Researchers found three findings. (1) Characteristics planning thematic learning include: mapping the themes closest attention to the environment with students from the easiest to the difficult, from the simple to the complex. (2)haracteristics of learning implementation thematic include: Theinitial activity is done to encourage students to profess more motivated to learn and explore the experience, the presentation of instructional materials using project methods, materials used are worksheets prepared by teachers, and the closing conclude the core of learning delivered, Learning implementation schedule that is less constrained division according to themes to be studied. (3) Characteristics of thematic learning evaluation using the results of performance, attitude, and knowledge. For the evaluation of UTS and UAS follow the official rules. Keywords: Planning, implementation, evaluation, learning, thematic